Resilient Governance Regimes That Support Urban Agriculture in Sub-Saharan Cities: Learning From Local Challenges - Vidal Merino, Mariana; Gajjar, Sumetee Pahwa; Subedi, Aasha; Polgar, Ana; Van Den Hoof, Catherine (Frontiers in Sustainable Food Systems, 2021)
Local governments in Sub-Saharan Africa face the daunting task of high urban growth and potentially devastating impacts of climate change across local communities and the economy. Urban and peri-urban food production can be among nature-based strategies planned for improving urban food security, reducing emissions, and climate adaptation. Co-operative governance, strategic planning, and accountable institutions are needed to support urban agriculture (UA), in the face of climate risks, unplanned urban development, the gendered nature of food provision, and the inability of urban farmers to self-organize toward optimal market and land access outcomes. Using a case study approach guided by qualitative content analysis with information derived from web analysis, we apply the Institutional Analysis and Development Framework to analyze underlying governance factors for UA in three selected Sub-Saharan African cities. Our three case cities of Kampala, Tamale and Cape Town reveal that UA is beginning to receive policy attention toward food security, and recognition for generating environmental, ecological, health, and human well-being benefits. Literature from specific cities however does not yet signal a local awareness and policy thrust regarding the associated and pertinent climate adaptation benefits of urban agriculture. We therefore recommend trans-disciplinary, locally-led, planning-based, and multi-sectoral approaches, involving a range of stakeholders toward recognizing and achieving the climate adaptation, environmental (ecologically restorative) and food security benefits of pursuing urban agriculture. This signals a larger role for the practice in sustainability discourse and SDGs 2 and 11, scaling out and up across large, medium and small towns, and cities of Sub-Saharan Africa.